Evaluation of Construction Project Performance Using the Earned Value Method (EVM): A Case Study of the Postgraduate Building Project of UIN Alauddin Makassar - Irma Aswani Ahmad; Aqilah Nabila Rezki; Ulmiah Muis; Nurlita Pertiwi; Nur Anny Suryaningsih Taufieq (Universitas Negeri Makassar, 2026)
This study aims to analyze the cost and schedule performance of the Postgraduate Building Construction Project of Alauddin State Islamic University Makassar using the Earned Value Method (EVM). The study employed a quantitative case study approach using project data, including the Bill of Quantities (BoQ), time schedule, S-curve, project progress reports, and actual project costs. The analysis used EVM indicators, namely Planned Value (PV), Earned Value (EV), Actual Cost (AC), Schedule Performance Index (SPI), Cost Performance Index (CPI), Schedule Variance (SV), and Cost Variance (CV). The results showed that a CPI value of 1 and a CV value of 0 indicated that project expenditures remained within the planned budget. However, the SPI value of 0.87 and negative SV value indicate that the project experienced delays, with project progress reaching only 87% of the planned target. The EVM method was effective in evaluating project performance by integrating cost, schedule, and work progress into a single analysis system. Keywords: Earned Value Method, construction project, cost performance, schedule performance, project control.